Drinking Water Source Protection in the Tampa Bay Region: A Guide for Government Officials - Amy L. Shober (EDIS)
SS524, a 4-page fact sheet by Amy L. Shober, familiarizes government officials in the Tampa Bay region with some of the regulatory and non-regulatory tools that can help to protect local sources of drinking water. Includes references. Published by the UF Department of Soil and Water Science, December 2009.